Loss-of-Function KCNE2 Variants: True Monogenic Culprits of Long-QT Syndrome or Proarrhythmic Variants Requiring Secondary Provocation?. (August 2017) - Roberts, Jason D.; Krahn, Andrew D.; Ackerman, Michael J.; Rohatgi, Ram K.; Moss, Arthur J.; Nazer, Babak; Tadros, Rafik; Gerull, Brenda; Sanatani, Shubhayan; Wijeyeratne, Yanushi D.; Baruteau, Alban-Elouen; Muir, Alison R.; et al.
Abstract : Background—: Insight into type 6 long-QT syndrome (LQT6), stemming from mutations in the KCNE2 -encoded voltage-gated channel β-subunit, is limited. We sought to further characterize its clinical phenotype. Methods and Results—: Individuals with reported pathogenic KCNE2 mutations identified during arrhythmia evaluation were collected from inherited arrhythmia clinics and the Rochester long-QT syndrome (LQTS) registry. Previously reported LQT6 cases were identified through a search of the MEDLINE database. Clinical features were assessed, while reported KCNE2 mutations were evaluated for genotype–phenotype segregation and classified according to the contemporary American College of Medical Genetics guidelines. Twenty-seven probands possessed reported pathogenic KCNE2 mutations, while a MEDLINE search identified 17 additional LQT6 cases providing clinical and genetic data. Sixteen probands had normal resting QTc values and only developed QT prolongation and malignant arrhythmias after exposure to QT-prolonging stressors, 10 had other LQTS pathogenic mutations, and 10 did not have an LQTS phenotype. Although the remaining 8 subjects had an LQTS phenotype, evidence suggested that the KCNE2 variant was not the underlying culprit. The collective frequency of KCNE2 variants implicated in LQT6 in the Exome Aggregation Consortium database was 1.4%, in comparison with a 0.0005% estimated clinical prevalence for LQT6. Conclusions—: On the basis of clinical phenotype, the high allelic frequencies of LQT6 mutations in the Exome Aggregation Consortium database, and absence of previous documentation of genotype–phenotype segregation, our findings suggest that many KCNE2 variants, and perhaps all, have been erroneously designated as LQTS-causative mutations. Instead, KCNE2 variants may confer proarrhythmic susceptibility when provoked by additional environmental/acquired or genetic factors, or both. Abstract : Supplemental Digital Content is available in the text.